PELATIHAN MANAJEMEN STRATEGI BAGI KEPALA SEKOLAH DAN GURU DALAM MENDORONG PEMBELAJARAN BERDIFERENSIASI DI KELAS - Yuli, Yuli Supriani (ALAINA: Jurnal Pengabdian Masyarakat, 2025)
This community service aims to enhance the understanding and skills of school principals and teachers in implementing differentiated learning through strategic management training. The method used is a qualitative approach with action research, which includes problem identification, solution development, training program design, implementation, and result evaluation. The training includes interactive discussions, hands-on practices, and reflections to improve participants' understanding and skills. The findings from this service show that the training successfully enhanced the principals' and teachers' ability to design differentiated learning that is more adaptive to students' needs. In conclusion, this training makes a significant contribution to improving the quality of more inclusive education and can serve as a model for other schools in implementing effective differentiated learning strategies.